Narrativas, agências e trajetórias : para uma etnobiografia de mulheres de quilombos de Chapada dos Guimarães/MT - Vithoft, Patricia Venzo Garcia (2018)
The ethnographic research explores narratives, agencies and trajectories of women from quilombos in Chapada dos Guimarães/MT. The concept of ethnobiography is engaged to analyze narrative not only as data source, re-dimensioning it as a way to acces s the experiences interpretations carried out by social agents. From this perspective, quilombola women, the narrative subjects, tell their experience in the world by what is meaningful to them, broadening the understanding of the quilombola social network in three dimensions of social relations: their own relations within their communities; the relations between communities and their relations with others, outside ethnic borders. The narratives give access to the quilombola social network, the dwelling places in the urban zone at the city of Chapada dos Guimarães and the social experiences of this population, previously expelled from their historical and traditional dwelling territories. The ethnography exposes the agency of four quilombola women, acting in different ways, as well as their lifes’ trajectories in different processes of compulsory displacement of their territories, rights claims and personal experiences. In such, the fieldwork was carried out through observation, dialogues, field notes and interviews, in order to register the narratives, the kinship relations, the exchange networks, the subsistence activities and the places of dwelling with their traditional knowledges. The research focus on the perspective of women from quilombos, living within or outside traditional territories, and how, through the narration of their experiences, they build their worlds, their identities and their relations